The Political Language of Minority Islam in the Indian State of Kerala: The Works of C.H. Mohammed Koya - Karinkurayil, Mohamed Shafeeq (2021)
Subaltern politics in India is usually studied outside the electoral process. This paper looks at a Muslim organization of enviable electoral success in the south Indian state of Kerala, the Indian Union Muslim League. By focusing on the works by the most iconic of its leaders, C.H. Mohammed Koya, this paper looks at the reconceptualization of minority politics in the context of Kerala. The paper illustrates that C. H. Mohammed Koya forges a new ethic of minority politics that reorients the minority subject with relation to the postcolonial state. The works under discussion posit the postcolonial minority subject in terms of the intelligibility of an assumed past and fashion itself in terms of giving and sacrifice, thereby assuming the role of the agent in the governmental state. An ideological position which masks the real condition of Muslim existence in the late ‘70s when it was written, its efficacy is in establishing a praxis for dignity and thereby imagining the Indian state not as an alien entity but as a mechanism which can be mastered.
Keywords: minority politics; Mimicry; electoral politics; Indian Union Muslim League; Kerala